Pengembangan Media Pembelajaran Matematika Berbasis Web Menggunakan Aplikasi Educandy untuk Meningkatkan Motivasi Belajar Siswa - Natalia, Natalia; Wahid, Sirojudin; Muchyidin, Arif (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2024)
This study aims to develop web-based learning media using the educandy application to increase student learning motivation at MTs Al Washliyah. The research method used is Research and Development (RD), using the ADDIE development model (analysis, design, development, implementation, evaluation). The learning media developed resulted in a web learning media product. This study used probability sampling with the cluster random sampling method and obtained a sample at MTs Al Washliyah Talun involving 20 seventh grade students. The data collection techniques used were questionnaires and unstructured interviews. The research instruments used in this study were expert validation questionnaire, student response questionnaire, student learning motivation questionnaire and pretest-posttest questionnaire.  The data analysis technique used was qualitative and quantitative data analysis. Qualitative data analysis is used to conduct theoretical studies and observations, while quantitative data analysis is used to calculate expert validation scores, student response questionnaires, student learning motivation questionnaires and N Gain tests. The results of this study indicate that the learning media developed is feasible to use based on expert validation with a very feasible category, and can effectively increase student learning motivation based on the results of the N Gain test and learning motivation questionnaire, and get a response with a very practical category.